The Role of Customer Trust Toward Digital Sales and Website Visitor Satisfaction on Customer Loyalty of Zara Indonesia - Sudirjo, Frans; Novita Sari, Efti; Yuliani; Hendra; Apramilda, Riesna (SEULANGA SYSTEM PUBLISHER, 2024)
This study examines the variables that affect e-trust and e-satisfaction and how they affect e-loyalty. This study employs a conclusive and descriptive research design, gathering data through survey-based methodologies. Researchers utilize a particular kind of survey called a questionnaire. Only one cross-sectional research design was used in this study. Non-probability sampling combined with a judgmental sampling strategy is the method employed for sampling. LISREL is used in this study to process data utilizing SEM methods. According to the research, e-satisfaction is significantly positively impacted by perceived delivery efficiency. It was discovered, nevertheless, that e-satisfaction was not considerably affected by website design. Aside from that, e-trust is not significantly impacted by website design. However, e-trust is significantly positively affected by online privacy and security perceptions. Furthermore, it was discovered that e-loyalty is significantly positively affected by e-satisfaction. Ultimately, it was found that e-trust significantly improves e-loyalty as well.